Pengaruh Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) terhadap Histologis Pankreas Mencit (Mus musculus L. Swiss Webster) yang Diinduksi Sukrosa - Ramadhan Sumarmin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Diabetes Mellitus (DM) is a metabolic disorder caused by lack of insulin which islet cells of Langerhans in the pancreas were damaged or decreased. DM treatment is quite expensive so it takes the alternative medicine. Ones of alternative medicine using Mangosteen Fruit pod. The pod of the mangosteen fruit have xanton flavonoid compounds, which function as antioxidants that can lower blood glucose levels and improve pancreatic cells. The study aimed to determine the effect of mangosteen rind extract (Garcinia mangostana L.) to display the pancreatic histology of mice (Mus musculus L. Swiss Webster) induced male sucrose. This study used Completely Randomized Design (CRD) with 5 treatments and 5 replications. treatments is P1 (positive control), sucrose 0.8 g/kg (negative control / P2), sucrose + 200 mg/kg of mangosteen peel extract (P3), sucrose + 400 g/kg of mangosteen peel extract ( P4), sucrose + 600 mg/kg of mangosteen peel extract (P5). Observations quantitatively to determine blood glucose levels and the number of Langerhans islet cells after 5 days and 4 days inducing the extract. Data were analyzed by ANOVA, if there is a difference will be continued with Duncan test at the 0.05 significance level. The results showed the average number of Langerhans islet cells 205.6 (P1), 134.0 cells (P2), 114.2 cells (P3), 193.0 cell (P4), and 181.8 cells (P5). From the results obtained in the analysis of data obtained Fhitung<Ftabel significant at 0.05, so it can be concluded that the mangosteen rind extract has no effect on pancreatic histological induced male mice sucrose.